Pemasaran Jasa Pendidikan Berbasis Mutu sebagai Upaya Peningkatan Kepercayaan Masyarakat pada Lembaga Pendidikan Islam Transformatif - Evy Ramadina; Sulistyorini Sulistyorini; Agus Eko Sujianto (Global Education Journal, 2026)
Educational service marketing has become a strategic aspect in enhancing the competitiveness of educational institutions, particularly within the context of transformative Islamic education, which emphasizes the integration of Islamic values and social transformation. However, marketing practices that are not quality-based often result in low levels of public trust in educational institutions. Therefore, this study aims to analyze quality-based educational service marketing as an effort to increase public trust in transformative Islamic educational institutions. This study employs a qualitative approach using a library research method. Data were collected through documentation from various relevant scientific sources, including accredited journals, books, and other supporting documents. The data analysis technique utilizes content analysis through stages of unitization, coding, categorization, and interpretation to produce a comprehensive conceptual synthesis. The results indicate that quality-based educational service marketing plays a significant role in building public trust through four main dimensions, namely input quality, process quality, output quality, and service quality. Public trust is formed through the consistency of service quality, transparency of information, institutional reputation, and user experience. In the context of transformative Islamic education, quality-based marketing is further strengthened by Islamic values, which serve as the main differentiating factor of educational institutions. In conclusion, quality-based educational service marketing is an effective and sustainable strategy for enhancing public trust. The integration of educational quality and value-based marketing strategies is key to building the competitive advantage of transformative Islamic educational institutions.